Corporate social responsibility and employee green behavior in the tourism industry with mediating role of organizational trust - Ta, Giang; Nguyen, Anh; Nguyen, Thao (Journal of Finance - Marketing Research, 2026)
In the context of tourism industry in Vietnam increasingly facing the demand for sustainable development, employee green behavior (EGB) is considered a core factor reflecting the level of transformation of organizational values into sustainable practices. This study aims to explore how employees' awareness of corporate social responsibility (CSR) affects green behavior at the workplace, with a focus on analyzing the mediating role of organizational trust (OT). Applying a qualitative research method combined with typical case studies at tourism enterprises in Xuan Huong Ward - Da Lat, this study conducted 15 in-depth semi-structured interviews and analyzed the themes in a reflective manner (Braun & Clarke, 2006). This results show that the transformation from CSR awareness to green behavior does not occur linearly, but through an emotional-moral layer, in which organizational trust plays the role of “invisible glue”, promoting value empathy and proactive behavior. Three main themes are drawn including: (1) CSR as an indicator of ethics and intrinsic commitment, (2) organizational trust as an emotional foundation for green behavior, and (3) green behavior as an expression of organizational attachment and professional identity. The study contributes to localizing the CSR–OT–EGB model in the context of Vietnamese organizational culture, while expanding the theory of ethical behavior in organizations through the lens of emotions and reflection.